Analyzing the Happiness Mysticism from Al-Ghazali’s Thought on People with Disabilities in the Modern Era - Nur Zaenab (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study explores the concept of happiness from the perspective of al-Ghazali’s mysticism and its relevance to people with disabilities in the modern era. Drawing on al-Ghazali’s theological, philosophical, and Sufi insights, the research examines how spiritual well-being, moral refinement, and closeness to God serve as core elements in achieving true happiness, beyond material or physical limitations. Using a qualitative descriptive approach, this study analyzes classical Islamic texts alongside contemporary literature on disability studies. The findings reveal that al-Ghazali’s emphasis on inner purification (tazkiyat al-nafs), gratitude, and patience offers a transformative framework for understanding happiness among individuals with disabilities. In the modern context, this mystical approach can help challenge societal stigma, promote inclusivity, and encourage a more holistic view of human flourishing. The research concludes that integrating al-Ghazali’s spiritual paradigm with contemporary perspectives on disability can foster both personal resilience and social acceptance, paving the way for a more compassionate and equitable society.